Excavations by K.M. Kenyon in Jerusalem 1961-1967 : Volume V Discoveries in Hellenistic to Ottoman Jerusalem Centenary volume: Kathleen M. Kenyon 1906-1978. - Prag, K. (Levant supplementary series., 2008)
Stratigraphic analysis of Site S. IV.